Pengaruh Program Corporate Social Responsibility (CSR) dan Citra Perusahaan Terhadap Loyalitas Pelanggan PT. Telkom Kandatel Yogyakarta - Nita Megayanti; Abdul Rohman (Jurnal Komunikasi)
Recently, consumers are more and more aware about the products that they use. Customer has also started to take more concern on the company background. This tendency has led companies to be more aware on building a positive image toward their customer. Companies are using social responsibility program to show their respect to their society and stakeholders. According to message design theory, CSR is a tool to build a positive image, which is expected to increase loyalty and to attract new customer in order to use the company products and services. This research is quantitative using Pearson's product moment and regression analysis. A significant positive correlation between CSR and customer loyalty, are shown by a correlation coefficient rxy=o.394 and a coefficient of determination 15.6%. There is also a significant positive correlation between corporate image and customer loyalty, shown by rxy=o.431 and a coefficient of determination 18.6%. Both CSR and corporate image will also positively correlated to customer loyalty, shown by a determination coefficient (adjusted R square) of 0.248, which suggest that CSR and corporate image would affect customer loyalty by 24.8%.